Focused ultrasound-induced blood-brain barrier opening promotes glioprotective phenotypes in ACSA-II+ murine astrocytes - Rebecca L. Noel; Alina R. Kline-Schoder; Alec J. Batts; Nancy Kwon; Fotios Tsitsos; Elisa E. Konofagou (iScience)
Summary: Focused ultrasound-induced blood-brain barrier opening (FUS-BBBO) is a well-established neuroimmune modulation and drug delivery enhancement tool capable of effecting cellular, cognitive, and pathological benefits in the brain. However, the cellular mechanisms underlying these bioeffects remain incompletely characterized, motivating the present study investigating the role of a critical glial cell type: astrocytes. Here, we use single-cell RNA sequencing and flow cytometry to characterize the phenotypic response of hippocampal astrocytes 2, 4, and 7 days after FUS-BBBO exposure in aged WT and Alzheimer’s disease mice. The data presented herein indicate that FUS-BBBO increases gene expression related to synapse modification, neurogenesis, ion transport, and neuronal development. Taken together, these data elucidate a glioprotective role for hippocampal astrocytes following FUS-BBBO, offering mechanistic context and support for previously observed benefits of FUS-BBBO. This evidence critically deepens our understanding of the cellular effects of FUS-BBBO as clinical adoption becomes more widespread.